THE USE OF BAMBOO FACADES’ FREQUENCY TO IMPROVE APARTMENT USER’S WELL-BEING - Tiffany Aurelia Ongkojoyo; Feny Elsiana; Liliany Sigit Arifin (DIMENSI (Journal of Architecture and Built Environment), 2023)
Noise from the road exceeding 40 dB disturbs the room atmosphere and quality of rest in an apartment. The aim of this research will utilize the wind to swing the kinetic facade to create background noise that supports the user's well-being. The aim of this research is to invent a kinetic façade system that supports the apartment user's well-being. To achieve this, the research utilizes wind to blow kinetic facades to produce background noise which also reduces glare from sunlight thereby improving well-being. Experiments were carried out by comparing the results of measuring frequencies of bamboo musical instruments with solfeggio frequencies. The bamboo musical instruments analyzed included 18 angklungs, 3 windchimes and 21 variations of bamboo models. The frequencies obtained by the final model are close to that of solfeggio frequencies, namely 432Hz, 639Hz, 747Hz and 852 Hz. This can reduce Daylight Glare Probability (DGP) by 13.36%, 9.69%, and 5.01%.